Plasma exchange in patients with myocarditis: comparison study. (25th November 2020) - Kulikova, V; Nedostup, A; Blagova, O; Nechaev, I; Ragimov, A; Kupriyanova, A; Zajdenov, V
Abstract: Background: Cardiac auto-antibodies (AABs) are detected frequently in patients with inflammatory dilated cardiomyopathy (iDCM) of arrhythmias due to myocarditis. Elimination of AABs with apheresis improves left ventricular function as well as the immunosuppressive drugs (ISDs) do. There is no data on the combined use of ISDs and apheresis. Aims: To investigate the clinical efficiency of plasma exchange (PE) in patients with myocarditis in comparison with patients without PE. Methods: There were 38 patients with iDCM under stable oral medication with maximal tolerated dose of β-blockers/angiotensin-converting enzyme inhibitor/aldosterone antagonists at least 3 month before study inclusion; and 48 patients with arrhythmias due to myocarditis resistant to antiarrhythmic drugs (AADs). Patients underwent evaluation including heart CT scan, MRI, endomyocardial biopsy, myocardial perfusion scan, and coronary angiography to diagnose myocarditis. All the patients had a high level of AABs against cardiac antigens. PE group were consisted of 19 patients with iDCM (left ventricular ejection fraction (LVEF) 35±7%) and 22 patients with arrhythmias (premature atrial (PACs) or ventricular (PVCs) contractions more than 3000/day or atrial fibrillation (AF)). All the patients in PE group underwent a single volume PE filled with 0.9% sodium chloride. Another 19 iDCM patients and 26 arrhythmic patients were controls without PE. Echocardiographic parameters, a 6-minute walk test (6MWT) distance, Holter monitoring and AABs level were assessed at baseline, 6 and 12 month follow-up. Some patients were treated by ISDs before PE. PE group patients got methylprednisolone (MP) significantly rare than controls after PE. The mean doses of MP were significantly lower than in controls too. Results: AABs level significantly decreased just after PE and during the follow-up only in PE group. iDCM patients also had significant improvement in LVEF 35±7% vs. 45±11% at a year follow up, and 6MWT distance in comparison with LVEF 33±7% vs. 37±11% at a year follow up in controls. There were 58% PE group patients with absolute LVEF improvement >10% classified as responders in comparison with 32% responders in controls. There were 86% PE group patients with arrhythmias in and 58% patients in control group who were classified as responders as they achieved a decrease of PAVs and PVCs or AF frequency >75% relative to baseline. AADs were eliminated in 46% PE group patients and in 23% control group patients with arrhythmias. We also tried to predict good response for PE in both iDCM and arrhythmic patients. iDCM responders were characterized by LVEF≤37% at baseline. Arrhythmic group responders were characterized by higher level of AABs to cardiac conduction cells antigens at baseline. Conclusions: PE improves both cardiac function and daily activities in patients with iDCM and arrhythmias due to myocarditis. PE is safe and high effective, and helps avoid using high doses of ISDs Funding Acknowledgement: Type of funding source: None